The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1038/hdy.1996.56
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for repression of somatic P element movements in Drosophila melanogaster consistent with a role for the KP element

Abstract: The P family of transposable elements in Drosophila melanogaster has, since its introduction into D. melanogaster populations in this century, diversified into a number of internally deleted forms. One of these, the KP element, is abundant in the genomes of flies from populations from Asia, Europe and Africa. There is some evidence that this sequence can act as a repressor of transposition. We have studied a mutation, singedv k(snvw) in which a KP element is one of two P elements inserted into the 5' exon of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Itoh and Boussy (2002) wondered whether this could be the final equilibrium state of the D. melanogaster genomes in nature, and suggested that further surveys of wild populations are required. These authors recommended these surveys especially because such predominance was not predicted by any of the theoretical models that have been carried out to evaluate P element population dynamics (Brookfield, 1991(Brookfield, , 1996Anxolabéhère, 1997, 1998). Moreover, our study shows that the Brazilian populations seem to be more similar to the Eurasian than the North American ones.…”
Section: Discussionmentioning
confidence: 99%
“…Itoh and Boussy (2002) wondered whether this could be the final equilibrium state of the D. melanogaster genomes in nature, and suggested that further surveys of wild populations are required. These authors recommended these surveys especially because such predominance was not predicted by any of the theoretical models that have been carried out to evaluate P element population dynamics (Brookfield, 1991(Brookfield, , 1996Anxolabéhère, 1997, 1998). Moreover, our study shows that the Brazilian populations seem to be more similar to the Eurasian than the North American ones.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to contradict the original observations of KP elements as specific to the genomes of M' (Black et al, 1987) or Q strains having biparentallytransmitted repression (Jackson et al, 1988). Genomic KP elements may not have a direct or large influence on the phenotypes in the P-M system, although individual KP elements have been shown to have the potential of repressing transposase activity (Andrew and Gloor, 1995;Lee et al, 1996;Brookfield, 1996a). Complete P elements, in contrast, are required as a source of transposase for P transposition induction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the majority of the P element sizes seen were those of entirely full‐size P and KP elements, as mentioned above. Third, KP elements appeared not as important as full‐size P elements in determination of P‐M phenotype, although the KP element was shown to have a repression potential of P transposition (Black et al ., 1987; Jackson et al ., 1988; Andrew & Gloor, 1995; Brookfield, 1996). KP elements were detected in all lines with a wide divergence in the phenotypes, whereas a line with no full‐size P element could not be P type, for example, KR‐7 (M′) in this study.…”
Section: Discussionmentioning
confidence: 99%